Mouse X-linked microRNA cluster regulates the meiotic checkpoint and Prdm9 -driven hybrid sterility in a copy number–dependent manner - Petr Jansa; Giordano Tanieli; Kim Vucinic; Diana Lustyk; Karel Fusek; Barbora Valiskova; Kento Morimoto; Seiya Mizuno; Kristian Ullrich; Linda Odenthal-Hesse; Jan Provaznik; Vladimir Benes; et al. (Proceedings of the National Academy of Sciences, 2025)
One of the reproductive barriers between diverging populations during formation of a new species is the sterility of their hybrids. The Prdm9- driven hybrid male sterility of Mus musculus musculus × Mus musculus domesticus hybrids depends on the interaction between PRDM9, a histone methyltransferase that determines the positions of meiotic recombination hotspots, and an as yet unknown X-linked genetic factor within the Hybrid sterility X2 ( Hstx2 ) locus. Here, we report that the Mir465 microRNA (miRNA) gene cluster is the predicted Hstx2 hybrid sterility factor. We show that removal of the Mir465 genes restores the fertility of sterile hybrids and improves meiotic synapsis of homologous chromosomes. Mir465 knockout also restores spermatogenesis in sterile chromosomal translocation carriers, demonstrating that Mir465 acts as a meiotic checkpoint that can be activated independently of Prdm9 intersubspecific incompatibility. Furthermore, the Mir465 knockout increases the global recombination rate in hybrids and in parental Mus m. domesticus mice. This demonstrates that Mir465 is responsible for the phenotypes of the two overlapping genetic loci, the Hstx2 engaged in fertility of hybrids and the Meiotic recombination 1 ( Meir1 ) controlling the recombination rate. The finding of enlarged Mir465 clusters in all European Mus m. musculus samples tested and the identification of differentially expressed targets suggest that the reproductive barrier between the two subspecies is sensitive to copy number variation of Mir465 genes. Together, the underdominant interaction between Prdm9 and Mir465 provides a rare example of Dobzhansky–Muller incompatibility in hybrids of closely related species, making it accessible for further analysis at the molecular level.